THE ROLE OF CUSTOMARY LAW AND ISLAMIC ECONOMIC LAW IN RESOLVING DEBT DISPUTES WITHIN THE COMMUNITY - Silpi Nadia Sari; Rassya Aulia Rahmadani; Nurmala; Sizo Karlita; Gina Raudatul Jannah; Bunga Juniarti Syahputri; Iinata Istahuna Putri; Erza Lianti; Nurlaila; Aulia; Riska Pebriani; Zaitun (International Journal of Multidisciplinary Reseach, 2025)
This study examines the role of customary law and Islamic economic law in resolving debt disputes within rural communities, highlighting the integration of socio-cultural norms and religious principles in legal practice. Using a qualitative case study approach in Olak Village, data were collected through interviews with customary leaders, religious figures, disputing parties, and village officials, as well as observation of deliberation forums and documentation review. The findings reveal that debt disputes are resolved through restorative and consensus-based mechanisms that prioritize reconciliation, social cohesion, and moral responsibility rather than punitive enforcement. Customary law provides social legitimacy and preserves communal harmony, while Islamic economic law offers ethical guidance grounded in justice, transparency, mutual consent, and the prohibition of usury. The study demonstrates that these two legal systems operate complementarily, forming a hybrid dispute resolution model that is culturally accepted, socially legitimate, and morally binding. This integrative approach enhances compliance, trust, and long-term accountability, reflecting the principles of legal pluralism and restorative justice in practice. The research underscores the significance of recognizing and strengthening customary–Islamic legal mechanisms as effective alternatives to formal litigation, with implications for policy, community development, and the sustainable management of economic relations in pluralistic societies.